The mega quiz - "Mitchelhill, Barbara" (London; Andersen Press, 2017)
"Damian Drooth is an ace detective, although sometimes he leaves the hard work to his friends so he can concentrate on the masterplan. When Damian hears about a Mega Quiz with an amazing prize, he decides to enter with his friends. This means paying an entrance fee. But all is not as it seems, and Damian is soon on the trail of a dastardly trickster." --Publisher description
Donated from "Book Planet", Dated 18-4-2025.
Keywords: Detective and mystery fiction-English